Enhanced proprioceptive acuity at the knee in the competitive athlete - Courtney, C. A.; Rine, R.; Jenk, D. T.; Collier, P. D.; Waters, A. (Journal of Orthopaedic & Sports Physical Therapy, 2013)
Controlled laboratory study: cross-sectional. OBJECTIVE: To determine if proprioception, measured by the threshold to detection of passive motion (TDPM), differed in individuals who regularly participate in moderate-intensity exercise for fitness as compared to individuals involved in high-intensity skilled exercise. BACKGROUND: Previous research has been equivocal as to whether exercise training is associated with superior proprioceptive acuity, in particular, exercise that includes dynamic postural challenges such as cutting and pivoting. METHODS: Two groups of 25 healthy individuals (18-32 years old) were recruited. One group consisted of individuals who performed moderate-activity level exercises for 5 to 10 hours per week. Participants in the other group performed high-activity level exercises, including high-speed cutting and pivoting activities, at least 10 hours per week. Proprioception was determined using TDPM, in which the knee was slowly extended or flexed at an angular velocity of 0.5°/s or less from a starting position of 40° of knee flexion. RESULTS: Individuals participating in competitive, high-intensity skilled exercise demonstrated better acuity (average of both limbs) of TDPM (mean ± SD, 0.81° ± 0.38°; P<.001) than those participating in moderate-intensity exercise for fitness (1.53° ± 0.58°). A low but statistically significant association (r = -0.38, P = .006) was found between weekly duration of exercise and proprioceptive threshold as measured by TDPM. CONCLUSION: These results suggest that perceptual thresholds of passive movement may be enhanced, depending on activity level and associated postural challenge, and that higher level and increased amount of exercise may promote enhanced neurosensory processing in these individuals. Consequently, high-intensity skilled training may deserve further emphasis in orthopaedic rehabilitation.